The Theme of Deception in the Book of Revelation Bringing Early Christian and Contemporary Thai Culture into Dialogue - Tipvarakankoon, Wiriya (Claremont Studies in New Testament and Christian Origins, 2017)
An exploration of the New Testament book of Revelation in the Thai context.